The effect of formulation with ginger (Zingiber officinale var. Roscoe) and different brewing techniques on physicochemical and organoleptic characteristics of cascara tea - Wenny Bekti Sunarharum; Ajeng Khorirodatul Djannah; Ngesti Ekaning Asih (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
The utilization of coffee cherry pulp, one of coffee processing waste, into Â tea (or known as cascara tea) is still limited regardless of its potential. Cascara tea flavor could be improved, such as by the addition of spices.Â Besides the addition of spices, the brewing techniques may also contribute to the properties of brewed cascara tea and consumer acceptance This study aimed to determine the effect of formulation (the ratio between cascara and ginger) and the different brewing techniques on the physicochemical and organoleptic characteristics of cascara tea. The best treatment was also determined. This study was conducted in Nested design with 2 factors i.e. brewing techniques (decoction and infusion) and ratio of cascara and ginger (9:1; 7:3; 5:5). Data analysis was performed using Minitab 17 and the best treatment was chosen by Multiple Attribute Zeleny method. The results showed that the ratio between cascara and ginger, as well as brewing techniques had a significant effect (Î± = 0.05) on total phenolic content, caffeine content, pH, color (L*, a* and b* value), and organoleptic parameter (except for taste, aftertaste, and overall). The best treatment was obtained from cascara tea with ratio of cascara and ginger =7: 3, brewed using the decoction technique. It offered total phenolic content of 27.73 mg GAE/g; caffeine content of 1.93 mg/g; pH of 6.1; Lightness (L*) 40.1; redness (a) 12.4; and yellowness (b*) 25.6.